Photon transport mediated by an atomic chain trapped along a photonic crystal waveguide - Song, Guo-Zhu (2018)
We theoretically investigate the transport properties of a weak coherent input field scattered by an ensemble of Λ-type atoms coupled to a one-dimensional photonic crystal waveguide. In our model, the atoms are randomly located in the lattice along the crystal axis. We analyze the transmission spectrum mediated by the tunable long-range atomic interactions and observe the highest-energy dip. The results show that the highest-energy dip location is associated with the number of the atoms, which provides an accurate measuring tool for the emitter-waveguide system. We also quantify the influence of a Gaussian inhomogeneous broadening and the dephasing on the transmission spectrum, concluding that the highest-energy dip is immune to both the inhomogeneous broadening and the dephasing. Furthermore, we study photon-photon correlations of the reflected field and observe quantum beats. With tremendous progress in coupling atoms to photonic crystal waveguides, our results may be experimentally realizable in the near future.